Data-Driven Marketing Management Competencies: Strategies for Performance Optimization in the Big Data Era - Safitri Nurhidayati; Tamam Rosid; Rahmawati (Journal of Novel Engineering Science and Technology, 2026)
The proliferation of big data technology has fundamentally changed the paradigm of marketing management, requiring a new competency framework for optimal performance outcomes. Despite extensive technological advances, significant gaps remain in understanding how data analytic competencies translate into measurable improvements in marketing performance. This study investigates the relationship between data-analytic-based marketing management competencies and performance optimization strategies in contemporary business environments, with particular emphasis on identifying critical competency dimensions and their impact on organizational marketing effectiveness. A mixed-methods approach was used, combining quantitative analysis of 847 marketing professionals from 156 Indonesian companies with qualitative interviews of senior marketing executives. Data collection employed validated instruments measuring analytic competencies, technology adoption, and performance metrics in Q2–Q4 2024. Findings revealed four critical competency dimensions: technical analytic proficiency (β=0.43, p<0.001), strategic data interpretation (β=0.38, p<0.001), cross-functional collaboration (β=0.32, p<0.01), and ethical data governance (β=0.28, p<0.01). Organizations with high analytic competency scores reported 34% higher marketing ROI and 28% greater efficiency in customer acquisition compared to low-competency counterparts. Data analytic competencies significantly influence marketing performance outcomes, with technical proficiency and strategic interpretation serving as primary drivers. This study provides empirical evidence supporting the adoption of competency-based frameworks in marketing management practice.